THE EFFECTIVENESS OF CONTROLLING METHODS FOR INVASIVE SPECIES MERREMIA PELTATA (L.) MERR. IN BUKIT BARISAN SELATAN NATIONAL PARK, LAMPUNG - Ivana Rindi Antika P; Afda Refani; Ishlahul Fikri; Nur Jamiah Rangkuti; Adhika Putra Agra Wijnana (Jurnal Hutan Tropis, 2026)
Deforestation and degradation in Bukit Barisan Selatan National Park (BBSNP) have facilitated the aggressive invasion of Merremia peltata. By 2020, reports indicated that the species had infested over 8,000 hectares, significantly disrupting ecosystem dynamics. Despite various management interventions, control efforts have yielded limited success, necessitating a comprehensive evaluation of current methods. This study assesses the effectiveness of M. peltata control methods using the Analytical Hierarchy Process (AHP) and identifies strategic alternatives through A'WOT analysis. Results indicate effectiveness ratings for mechanical (46.67%), chemical (44.88%), biological (34.92%), and social (55.22%) methods. Although the social approach achieved the highest value, it remains classified as "less effective" according to the study's criteria. These findings suggest that current standalone efforts are insufficient. The analysis identifies the integration of control strategies as the primary priority, with an acquisition value of 59.7%. Consequently, optimizing control activities in BBSNP requires a multi-faceted, integrated management framework to improve ecological outcomes.